Fatores de risco cardiovascular em mulheres com antecedente de pré-eclâmpsia e sua associação com hipertrofia miocárdica e espessamento médio-intimal de carótidas - Ferreira, Ricardo Mattos [UNESP] (2016)
Background: A history of preeclampsia (PE) has been associated with cardiovascular disease in women. There is substantial evidence that cardiovascular alterations resulting from PE can persist even after termination of pregnancy. Objectives: 1-evaluate the frequency of cardiovascular risk factors in women with 12-month history of PE and their association with myocardial hypertrophy and carotid intima-media thickness (CIMT); 2-evaluate the effect of myocardial hypertrophy on left ventricular function and functional capacity. Methods: Transversal prospective study including 118 consecutive patients with 12-month PE history. Clinical and laboratory evaluations, echocardiogram, ergometric and carotid ultrasound were performed. Myocardial hypertrophy (LVH) was defined as indexed myocardial mass ≥ 45 g/m2,7. CMIT was considered elevated when the measures were above the 75th percentile for the age range. The classical risk factors for cardiovascular disease were considered, and the 30-year global cardiovascular risk score was calculated (GCVR_30). The data were analyzed by linear or logistic regression and Spearman’s correlation coefficient. Significance level p<0.05. Results: Systemic arterial hypertension (SAH) was identified in 52 patients (44%), overweight/obesity (OOB) in 82 (69%), dyslipidemia in 68 (57%) and metabolic syndrome in 47 patients (40%). A total of 48 women (41%) presented GCVR _30 greater than or equal to 10%, with these patients aged 34±5.4 years. LVH was present in 35 cases (29%) and associated with the presence of OOB (OR=4.51; CI95%:1.18 – 17.17, p<0.001), in a model corrected for age and SAH diagnosis. When only the metabolic syndrome components were analyzed, in the multiple logistic regression model, the abdominal circumference was the only clinical variable that showed association with LVH presence (OR=17.65; CI95%:3.70 – 84.17; p<0.001). Elevated CIMT was observed in 32 cases (27%), association was found between CIMT and GCVR _30 (R=0.381; p<0.001) and LVH presence was observed (OR:0.123; CI95%:0.046 – 0.330; p<0.001). Indices of diastolic function and myocardial mass were significantly associated with functional capacity. Conclusions: Twelve months after the PE event there is a high prevalence of cardiovascular risk factors. Furthermore, elevated LVH frequency was observed, which was associated with alterations of diastolic function indices and with harm to functional capacity. Among the risk factors, overweight and increased abdominal circumference play a prominent role in elevating the risk of myocardial hypertrophy 12 months after a PE episode. The GCVR _30 was associated with higher CIMT values. Data obtained in a simple manner, via anamnesis and physical exam, can be utilized to stratify myocardial hypertrophy risk, helping to identify patients of greater cardiovascular risk in this population.